Дослідження фотолюмінесценції пористого кремнію як фотосенсибілізатора генерації синглетного кисню - Timoshenko, V.Yu. (Publishing house "Academperiodika", 2022)
Si nanocrystals with dimensions of about several nanometers in layers and powders of porous silicon (por-Si) act as photosensitizers of the generation of singlet oxygen which is a highly chemical reactive form of molecular oxygen. The photosensitized mechanism and the efficiency are investigated by means of the photoluminescence spectroscopy. The experimental data are discussed in view of possible biomedical applications of por-Si.